Overt gastrointestinal bleeding because of hookworm infection - Chen, Jia-Min; Zhang, Xin-Mei; Wang, Liang-Jing; Chen, Yan; Du, Qin; Cai, Jian-Ting (Asian Pacific journal of tropical medicine, 2012)
<正>Hookworm infection is a relatively common cause of anemia in endemic areas.The most common hookworm species are Ancylostoma duodenale and Necator americanus.In this report we present a case of overt gastrointestinal bleeding Wause of hookworm infection.Capsule endoscopy revealed many hookworms in the lumen of proximal jejunum where active bleeding was seen. The patient was successfully treated with Albendazole.